Academic evasion in the Dentistry course of a public institution and actions to mitigate student dropout - Carmo Filho, José Ronildo Lins do (2023)
The study investigated aspects of evasion and evaluated the satisfaction of freshmen in the Dentistry course at a public higher education institution, in addition to reporting interventions to combat academic dropout developed during this period. This is a study with an observational, cross-sectional, descriptive, quantitative and qualitative phase, with the application of questionnaires; and another interventionist, with activities aimed at combating evasion. 74 students were interviewed, enrolled in the first year of the course, aged between 15 and 30 years old. Data were expressed as absolute and percentage frequencies and analyzed using Fisher's exact test or Pearson's chi-square test (p ≤ 0.05). Variables with significant association were submitted to the multinomial logistic regression model (RLM). It was observed that the degree of dissatisfaction with the course was higher among students with a lower age group (between 15 and 20 years old) and lower family income (up to 2 minimum wages). In addition, around 66% of possible dropouts had not yet had any kind of practical dental experience, while 69% of those intending to complete the course had already had some contact with clinical experiences. The RLM revealed that Dentistry not being the first option increases the probability of dropping out of the course by 7.96 times, regardless of the semester. There was also a reduction in dropout rates as interventions were carried out (lab coat ceremony, guided clinical visit and sponsorship of freshman students) were performed. It is concluded that the actions implemented to combat dropout in the Dentistry course had a positive impact on the dropout rates of the course in the analyzed semesters.